Comparative Transcriptome and Weighted Gene Co-expression Network Analysis Identify Key Transcription Factors of Rosa chinensis ‘Old Blush’ After Exposure to a Gradual Drought Stress Followed by Recovery - Jia, Xin; Feng, Hui; Bu, Yanhua; Ji, Naizhe; Lyu, Yingmin; Zhao, Shiwei (Frontiers in Genetics, 2021)
Rose is one of the most important ornamental crops, but drought limits its yield and quality seriously. The key transcription factors (TFs) and co-expression networks during rose’s responding to drought stress and recovery after drought stress is still limited. In this study, the transcriptomes of leaves of two-year-old cutting seedlings of Rosa chinensis ’Old Blush’ from three continuous droughted stages (30, 60, 90 days after full watering) and rewatering were analyzed using RNA sequencing. Meanwhile, weighted gene co-expression network analysis (WGCNA) was used to construct a co-expression network associated with the physiological traits of drought response to discover the hub TFs involved in drought response. More than 45 million high-quality clean reads were generated from samples and used for comparison with the rose reference genome. A total of 46433 differentially expressed genes (DEGs) were identified. Gene ontology (GO) term enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that drought stress caused significant changes in signal transduction, plant hormones, primary and secondary metabolism, and a certain degree of recovery after rewatering. Gene co-expression analysis identified 18 modules, in which four modules have highly degree of correlation with physiological traits. In addition, fourty-two TFs including members of NACs, WRKYs, MYBs, AP2/ERFs, ARFs and bHLHs with high connectivity in navajowhite1 and blue modules were screened. This study provided the transcriptome sequencing report of the drought stress and rewatering in R.chinensis ‘Old Blush’, and also identified candidate TFs in response to drought stress, providing clues for improving the drought tolerance of the rose through molecular breeding in the future.